Monoculture on the intellectual landscape: research performance evaluation. (1st July 2010) - Ruth, Damian
Abstract : The metaphor of 'monoculture on the intellectual landscape' is used to analyse the effects of large-scale research management regimes. The metaphor of 'monoculture on the intellectual landscape', derived from Shiva's 'monocultures of the mind', is developed and illustrated with respect to gender and ethnicity. The paper then discusses the production of knowledge in the context of monocultures of the mind, and concludes that large-scale research management regimes are inimical to healthy and diverse intellectual habitats.